Understanding the Impacts of Organizational Justice and Job Performance on Engagement among Employees in the Manufacturing Company - Naiemah et al., Saraih Ummi (International Journal of Advanced Science and Technology, 2019)
Employee engagement is crucial to be studied because it is a key factor to achieve the competitive advantage and the successful of the organization. Thus, this research aims to investigate the impacts of two determinants of employee engagement, namely organizational justice and job performance among employees in one of the Northern manufacturing company located in Malaysia.Quantitative approach has been utilized in this research. Data is collected from 160 respondents and has been analyzed by using the SPSS. The respondents completed measures of organizational justice, job performance and employee engagement in the self-rating perspectives. Results presented that there is a high level of employee engagement among employees in this company. Regression analyses also confirmed the significant impacts of organizational justice and job performance on engagement among employees in this company. Good appearance of perceived justice can enhance the higher level of employees’engagement. Also, this research revealed that an effective performance among the employees can contribute to the development of stronger perceptions of employee engagement. This study represents the ﬁrst attempt to empirically integrated and tested on organizational justice, job performance and employee engagement among the manufacturing employees.